Чинники формування уявлень жінки про материнство та трансформація образу матері в період народження дитини - Чепелєва, Н. І.; Chepelieva, N. I.; Надія Чепелєва (Габітус. - 2023. - Вип. 45. - С. 278-283, 2023)
Розглянуто чинники формування уявлень жінки про материнство, становлення материнської сфери, визначено особливості розвитку суб’єктивного ставлення жінок до материнської ролі, майбутньої дитини та об’єктивізація цих уявлень при народженні дитини. Акцентовано увагу на тому, що в період народження та в подальшому, під час безпосередньої реалізації материнської ролі, яскраво постає розбіжність між уявленням про материнство і реальним виконанням даної ролі. Проаналізовано основні чинники, які впливають на трансформацію образу матері в період народження дитини, на емоційний стан матері після народження дитини. Основним чинником узгодження уявлень і безпосереднього виконання материнської ролі визначено психологічну готовність до материнства, що проявляється як відповідальне чи інфантильне чи негативне ставлення до материнства.

The article examines the factors of the formation of women’s ideas about motherhood, the formation of the maternal sphere, the peculiarities of the development of the subjective attitude of women to the maternal role, the future child, and the objectification of these ideas at the birth of a child. Motherhood, as a psychosocial phenomenon, should be considered from two positions: maternal love as the provision of conditions for the child’s development and maternal love as part of a woman’s personal sphere. Motherhood is an important aspect of a woman’s personal identity, in the context of the conducted analysis, a conscious attitude to motherhood is considered by scientists as an integral psychological property of a woman’s personality, which is based on awareness of one’s own life choices and readiness to take responsibility for the performance of maternal functions. The analyzed scientific material allows us to assert that the idea and position of motherhood are formed long before the direct acquisition of the experience of motherhood, under the influence of many social and individual factors – the influence of society through social stereotypes and the mass media, in the form of attitudes and requirements towards motherhood for a certain period of time, the influence of the social circle, the experience of growing up in the parental family, and these representations are to some extent idealized. The article focuses on the fact that during the period of birth and later, when the mother’s role is directly realized, the discrepancy between the idea of motherhood and the actual performance of this role clearly appears. The main factors that affect the transformation of the image of the mother during the birth of the child and the emotional state of the mother after the birth of the child are analyzed. Psychological readiness for motherhood, which manifests itself as a responsible or infantile or negative attitude to motherhood, is defined as the main factor in the reconciliation of ideas and the direct performance of the maternal role.

Рассмотрены факторы формирования представлений женщины о материнстве, становления материнской сферы, определены особенности развития субъективного отношения женщин к материнской роли, будущему ребенку и объективизации этих представлений при рождении ребенка. Акцентировано внимание на том, что в период рождения и в дальнейшем, при непосредственной реализации материнской роли, ярко возникает разногласие между представлением о материнстве и реальным исполнением данной роли. Проанализированы основные факторы, влияющие на трансформацию образа матери в период рождения ребенка, эмоциональное состояние матери после рождения ребенка. Основным фактором согласования представлений и непосредственного исполнения материнской роли определена психологическая готовность к материнству, которая проявляется как ответственное или инфантильное, или отрицательное отношение к материнству.
Factors forming a woman’s perceptions about maternity and transformation of the image of the mother during childbirth
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; материнство; motherhood; материнська роль; maternal role; материнская роль; уявлення про материнство; conception of motherhood; представление о материнстве; психологічна готовність; psychological readiness; психологическая готовность; батьківське ставлення